Cassava brown streak virus Ham1 protein hydrolyses mutagenic nucleotides and is a necrosis determinant - Tomlinson, Katie R.; Pablo-Rodriguez, José Luis; Bunawan, Hamidun; Nanyiti, Sarah; Green, Patrick; Miller, Josie; Alicai, Titus; Seal, Susan E.; Bailey, Andy M.; Foster, Gary D. (Molecular plant pathology, 2019)
Cassava brown streak disease (CBSD) is a leading cause of cassava losses in East and Central Africa, and is currently having a severe impact on food security. The disease is caused by two viruses within the Potyviridae family: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV), which both encode atypical Ham1 proteins with highly conserved inosine triphosphate (ITP) pyrophosphohydrolase (ITPase) domains. ITPase proteins are widely encoded by plant, animal, and archaea. They selectively hydrolyse mutagenic nucleotide triphosphates to prevent their incorporation into nucleic acid and thereby function to reduce mutation rates. It has previously been hypothesized that U/CBSVs encode Ham1 proteins with ITPase activity to reduce viral mutation rates during infection. In this study, we investigate the potential roles of U/ CBSV Ham1 proteins. We show that both CBSV and UCBSV Ham1 proteins have ITPase activities through in vitro enzyme assays. Deep-sequencing experiments found no evidence of the U/CBSV Ham1 proteins providing mutagenic protection during infections of Nicotiana hosts. Manipulations of the CBSV_Tanza infectious clone were performed, including a Ham1 deletion, ITPase point mutations, and UCBSV Ham1 chimera. Unlike severely necrotic wild-type CBSV_Tanza infections, infections of Nicotiana benthamiana with the manipulated CBSV infectious clones do not develop necrosis, indicating that that the CBSV Ham1 is a necrosis determinant. We propose that the presence of U/CBSV Ham1 proteins with highly conserved ITPase motifs indicates that they serve highly selectable functions during infections of cassava and may represent a euphorbia host adaptation that could be targeted in antiviral strategies.
Keywords: Cassava; Cassava brown streak disease; Cassava brown streak virus; Food security; Ugandan cassava brown streak virus; Virus